Cretaceous calcareous dinoflagellate cysts as recorder of [delta] δ44/40Caseawater and paleo-temperature using Sr/Ca thermometry - Gussone, Nikolaus C.; Friedrich, Oliver (Chemical geology, 2018)
We evaluate the potential of calcareous dinoflagellates as archives for Sr/Ca-based paleo-temperature reconstructions and δ44/40Caseawater fluctuations on sediments from Ocean Drilling Program Expedition 113 (Hole 690C, Weddell Sea, Southern Ocean). Between 73 and 68Ma, Sr/Ca ratios of two Cretaceous dinoflagellate species, Pirumella krasheninnikovii and Orthopithonella globosa show a pronounced decrease, consistent with a significant drop in sea-surface temperature as reflected by the δ18O of planktic foraminifers. The apparent temperature sensitivity of the dinoflagellate cysts' Sr/Ca is ~0.06 and ~0.08mmol/mol°C−1, using δ18O-derived paleo sea-surface temperatures, which is significant and large enough to resolve paleoenvironmental temperature changes at current analytical precision. As the chemical composition of the cyst calcite appears to have a good preservation, the Sr/Ca of calcareous dinoflagellates has a potential to serve as paleo-temperature proxy, although the chemical composition of the Cretaceous seawater and potential impacts on the cyst geochemistry is pending further inspection. The Ca isotope composition of the two dinoflagellate species shows identical trends of increasing δ44/40Ca between 73 and 67Ma. The planktic foraminifer Archaeoglobigerina australis and the benthic foraminifer Nuttallides truempyi reveal the same increase of about 0.4‰ but are offset relative to the dinoflagellates by about +0.5‰, presumably due to species-specific Ca isotope fractionation. Bulk carbonate sediment shows significant scatter, likely caused by changes in faunal composition and does not reproduce the trend revealed by the dinoflagellate and foraminifer records. These observations demonstrate the importance of taxon-specific records and careful determination of fractionation factors of selected archives and highlight complications arising from utilizing less suitable archives, such as bulk sediments, for δ44/40Caseawater reconstructions. Our records indicate strong changes in the marine Ca cycle associated with the global temperature decrease towards the end of the Cretaceous.
Im Titel ist [delta] als griechischer Buchstabe dargestellt, die Zahlen danach sind hochgesetzt und seawater ist tiefgesetzt
Gesehen am 15.08.2019